2005
DOI: 10.1042/cs20050030
|View full text |Cite
|
Sign up to set email alerts
|

ATP-binding cassette transporter G8 M429V polymorphism as a novel genetic marker of higher cholesterol absorption in hypercholesterolaemic Japanese subjects

Abstract: The ratio of serum plant sterols to cholesterol is positively correlated with the fractional cholesterol absorption, whereas serum precursors of cholesterol synthesis are positively correlated with cholesterol synthesis. Recently, two ABC (ATP-binding cassette) transporters, ABCG5 and ABCG8, have been described as playing an important role in the absorption and excretion of sterols. In the present study, we tested the hypothesis that genetic variation in ABCG5/ABCG8 influences the levels of serum plant sterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 25 publications
2
31
3
Order By: Relevance
“…They concluded that women carriers of GG genotype showed stables levels of cholesterol and non response to dietary changes; however, carriers of AA genotype had a mayor reduction in plasma cholesterol between 1988 and 1996. On the other hand, our results for this polymorphism differ with Miwa et al (2005) who did not find any association with this genetic variant and lipid levels in patients from Japan. Similarly, Wang et al (2007) did not find significant differences in plasma and biliary lipid levels.…”
Section: Discussioncontrasting
confidence: 55%
“…They concluded that women carriers of GG genotype showed stables levels of cholesterol and non response to dietary changes; however, carriers of AA genotype had a mayor reduction in plasma cholesterol between 1988 and 1996. On the other hand, our results for this polymorphism differ with Miwa et al (2005) who did not find any association with this genetic variant and lipid levels in patients from Japan. Similarly, Wang et al (2007) did not find significant differences in plasma and biliary lipid levels.…”
Section: Discussioncontrasting
confidence: 55%
“…The remaining three studies did not report the ethnicity of the study subjects ( 9,12,33 ). The majority of the studies were conducted in mildly hypercholesterolaemic, otherwise healthy populations ( 5,12,13,27,28,(31)(32)(33). Five studies evaluated normocholesterolaemic subjects ( 9,11,29,30 ); two studies evaluated both ( 8,30 ).…”
Section: Meta-analysis: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The number of study participants ranged from 26 to 1,046. Five studies were conducted in a population of Caucasians ( 5,7,11,13,27 ), three studies investigated Asian populations ( 8,28,29 ), two studies were conducted in a Hispanic population ( 30 ), and two in a mixed racial population ( 31,32 ). The remaining three studies did not report the ethnicity of the study subjects ( 9,12,33 ).…”
Section: Meta-analysis: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been associated with premature coronary atherosclerosis and death (Hubá-ček et al 2001). Common sequence variations in the ABCG5 and ABCG8 genes have been reported to account for the variability in cholesterol and phytosterol absorption Plat et al 2005;Hubáček et al 2004;Miwa et al 2005;Weggemans et al 2002). Although a clear link has been established between ABCG5/ABCG8 genes and modification of the absorption and/or synthesis of plant sterols, there is still no consensus on the association of plasma total cholesterol and ABCG5/ABCG8 gene polymorphisms (Sehayek et al 2004;Berge et al 2002).…”
Section: Introductionmentioning
confidence: 99%